2002
DOI: 10.1111/j.1151-2916.2002.tb00571.x
|View full text |Cite
|
Sign up to set email alerts
|

Potential and Impedance Imaging of Polycrystalline BiFeO3 Ceramics

Abstract: Electrostatic-force-sensitive scanning probe microscopy (SPM) is used to investigate grain boundary behavior in polycrystalline BiFeO 3 ceramics. Scanning surface potential microscopy (SSPM) of a laterally biased sample exhibits potential drops due to resistive barriers at the grain boundaries. In this technique, the tips acts as a moving voltage probe detecting local variations of potential associated with the ohmic losses within the grains and at the grain boundaries. An approach for the quantification of gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(62 citation statements)
references
References 33 publications
2
60
0
Order By: Relevance
“…22 All these phenomena often make it difficult to detect the FE-PE transition by electrical investigations. The diffuse character of the phase transition can be understood in terms of the inhomogeneous composition both in A and B sites of the ABO 3 perovskite cell. "…”
Section: Resultsmentioning
confidence: 99%
“…22 All these phenomena often make it difficult to detect the FE-PE transition by electrical investigations. The diffuse character of the phase transition can be understood in terms of the inhomogeneous composition both in A and B sites of the ABO 3 perovskite cell. "…”
Section: Resultsmentioning
confidence: 99%
“…Important scientific possibilities offered by the above-mentioned techniques prompted worldwide effort to combine them. Fundamental research in this field was documented by Kalinin et al [19][20][21] and O'Hayre et al [22,23]. Two distinct techniques were proposed, namely, impedance imaging and spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…and Chen et al adopted short time (6h.). When iron oxides are prepared in FeSO 4 or FeCl 2 solution, in low pH solution iron oxyhyroxides are precipitated and in higher pH solution iron oxides can be crystallized 14) . In this work an oxyhyroxide or oxynitrate including bismuth and iron atoms may be crystallized in lower concentration of KOH solution and BFO can be prepared by increasing concentration of KOH.…”
Section: Experimentalsmentioning
confidence: 99%
“…BFO has been studied extensively for preparation and multiferroic properties [3][4] . In 2007 it was reported that BFO had photocatalytic activity under visible light irradiation 5) .…”
Section: Introductionmentioning
confidence: 99%